The effect of mild steel immersion time on synergistic corrosion inhibitor ability of terminalia catappa leaves extract - Arief Rafik; Sri Agustina; Marta Pramudita (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2022)
Inhibitors from natural materials are safe for the environment to replace chemical inhibitors in inhibiting corrosion. The tannin compounds contained in the Terminalia Catappa leaves extract have the ability to inhibit the corrosion rate. This study aims to determine the ability of Terminalia Catappa leaves extract and its synergism with KI in inhibiting the corrosion rate of mild steel metal. Mild steel that has been sanded and cleaned is then immersed in demineralized water. The immersion time was carried out in 3 variations which were 1, 3, and 5 hours. The weight-loss method is used to calculate the corrosion rate. The lowest corrosion rate was obtained at 0.0018 mmpy at immersion for an hour, and the concentration of inhibitor was 1250 ppm. The highest inhibition efficiency was obtained at 90% in immersion for an hour with a 1250 ppm inhibitor concentration. Inhibitor dari bahan alam digunakan karena aman bagi lingkungan untuk menggantikan inhibitor bahan kimia dalam menghambat laju korosi. Senyawa tanin yang terkandung pada ekstrak daun ketapang memiliki kemampuan untuk menghambat laju korosi. Penelitian ini bertujuan untuk mengetahui kemampuan ekstrak daun ketapang dan sinergisitas dengan KI dalam menghambat laju korosi pada logam mild steel. Mild steel yang telah diamplas dan dibersihkan kemudian direndam ke dalam media korosif yaitu air demineralisasi. Waktu perendaman dilakukan pada 3 variasi waktu yaitu, 1, 3, dan 5 jam. Metode weight loss digunakan untuk menghitung laju korosi. Laju korosi terendah didapatkan sebesar 0.0018 mmpy pada perendaman selama 1 jam dan konsentrasi inhibitor 1250 ppm. Efisensi inhibisi tertinggi didapatkan sebesar 90% pada perendaman selama 1 jam dengan konsentrasi inhibitor 1250 ppm.